Control brain machine interface for a power wheelchair - Hema, Chengalvarayan Radhakrishnamurthy; Murugesa Pandiyan, Paulraj, Assoc. Prof. Dr. (Springer-Verlag, 2011)
Link to publisher's homepage at http://www.springerlink.com/